1975
DOI: 10.1111/j.1745-6584.1975.tb03609.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Flora of Saline Aquifersa

Abstract: The bacterial flora of three unpolluted saline aquifers were examined. Aerobic, anaerobic, and facultative microorganisms were isolated and classified to genus. The organisms isolated were those commonly found in surface water and soil. Methanogenic bacteria were present in all aquifers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Along with this, the notion has developed that microbial activity plays a major role in the development and decay of contaminant plumes. Previous studies [Dockins et al, 1980;McNabb and Dunlap, 1975;Olson et al, 1981;Willis et al;1975] have documented the presence of diverse microbial populations in subsurface hydrologic systems and have suggested that most microbes grow in colonies attached to solid surfaces rather than as attached uniform films or free-floating organisms suspended in the liquid phase [Rittrnan and McCatry, 1980;Ghiorse and Balkwill, 1983;Wilson et al, 1983]. However, relatively little is known concerning the growth dynamics of these subsurface colonies and the resulting biological degradation rates of organic contaminants [Bitton and Gerba, 1984].…”
Section: Introductionmentioning
confidence: 99%
“…Along with this, the notion has developed that microbial activity plays a major role in the development and decay of contaminant plumes. Previous studies [Dockins et al, 1980;McNabb and Dunlap, 1975;Olson et al, 1981;Willis et al;1975] have documented the presence of diverse microbial populations in subsurface hydrologic systems and have suggested that most microbes grow in colonies attached to solid surfaces rather than as attached uniform films or free-floating organisms suspended in the liquid phase [Rittrnan and McCatry, 1980;Ghiorse and Balkwill, 1983;Wilson et al, 1983]. However, relatively little is known concerning the growth dynamics of these subsurface colonies and the resulting biological degradation rates of organic contaminants [Bitton and Gerba, 1984].…”
Section: Introductionmentioning
confidence: 99%